Vo2Max and Agility to Futsal Dribbling Technique Skills - Muhamad Anggie Haryesa; Fatah Nurdin; Iman Sulaiman (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
This study aims to determine the effect of VO2max and agility on basic futsal technical skills. This study is a regression correlation study on how much influence the VO2max variable and the agility variable have on dribbling skills. The study population was the students who took futsal extracurricular activities at SMP Negeri 9 Malang. The samples were taken by random sampling. The number of samples used was 35 students who took futsal extracurricular activities. The results of this research partially indicate that there is a negative and significant effect (p> 0.05) of VO2max on ball dribbling skills as indicated by the t test results of -8.969 with a regression coefficient of -0.135, and agility towards ball dribbling skills is shown from the t test results of 2,416 with a regression coefficient of 2,333. There is a significant effect (p <0.05) of agility on ball dribbling skills as indicated by the t test results of 2.416 with a regression coefficient of 0.106. Meanwhile, simultaneously (simultaneously) on the ball dribbling skills a significant effect is shown by the F value of 51.477. Based on the results of data analysis in research on VO2max and agility towards ball dribbling skills, it can be concluded that collectively (simultaneously) there is a significant effect on the level of cardiovascular endurance (VO2Max) and Agility on the dribbling skills of futsal extracurricular members of SMP Negeri 9 Malang.